Pemanfaatan Artificial Intelligence Dalam Meningkatkan Hasil Belajar Pendidikan Agama Kristen di Sekolah - David Christ Arjo (JPT : Jurnal Pendidikan Tematik, 2025)
The development of the Industrial Revolution 4.0 has brought Artificial Intelligence (AI) technology into the world of education, including in Christian Religious Education (PAK) learning, which has previously seemed boring for Generation Z. This study aims to examine how AI is used to improve PAK learning outcomes in schools and determine the important role of teachers in the digital era. This study uses a qualitative method with a descriptive analytical approach through a literature study from 2020 to 2025. The results show that the use of AI functions as a digital tool in an adaptive learning system that helps students understand complex religious concepts according to their abilities. The use of AI has increased student participation and made the learning process more efficient, but its success depends heavily on the teacher's ability to combine technology, pedagogy, and teaching materials. PAK teachers have a crucial role as facilitators, mentors, and ethical guardians to ensure that the use of technology remains in accordance with biblical teachings and the guidance of the Holy Spirit. In conclusion, by collaborating between AI technology and the strategic role of teachers, a dynamic and changing PAK learning environment can be created, while still maintaining the values ​​of Christian character development.